EVALUATION OF ANTI INFLAMMATORY ACTIVITY OF PHYLLANTHUS LONGIFLORUS IN EXPERIMENTAL ANIMAL MODELS - M. JESUPILLAI; P.THILLAI ARASU (International Journal of Pharma and Bio Sciences, 2014)
Anti inflammatory potential of aerial parts of Phyllanthus longiflorus was investigated in the present study using acute and chronic inflammatory models. Carrageenan, dextran and formalin were used as an edematogenic agent to induce hind paw edema in rats and the mean increase in paw volume were measured using plethysmometer. Results showed that methanol extract of Phyllanthus longiflorus at the doses of 100 and 200 mg/kg body weight significantly reduced in hind paw edema induced by Carrageenan, dextran and formalin. Therefore, it is concluded that Phyllanthus longiflorus is useful in the management of inflammatory diseases.